How much financial literacy matters? A simulation of potential influences on inequality levels - Giovanni Gallo; Alessia Sconti (Global Labor Organization (GLO), 2023)
This paper aims to identify the potential influence of financial literacy's marginal change on households' income (wealth) inequality levels both at the mean value and along with the distribution value. Using data from the Bank of Italy Survey of Households Income and Wealth (SHIW)'s 2016 wave - which includes the Big Three questions, a widely used measure of financial literacy - we show that replacing 10% of respondents reporting no correct answers with respondents reporting two correct answers out of three correct answers would increase the mean value of the household equivalized disposable income by 0.8% (160 exteuro per year). Additionally, the mean value would increase by +1.5% (285 exteuro per year) if we replace 10% of respondents reporting no correct answers with those reporting three correct answers. These results are not trivial. A lump sum leading to the same household income increase would cost on average EUR 4.1 to 7.3 billion per year in Italy. Finally, heterogeneous analysis reveals that an increase in financial literacy levels is expected to have different outcomes across the population, engendering often a greater reduction of inequality levels among the most vulnerable groups. As a natural policy implication, our results strongly support mandatory financial education in schools.
Keywords: D31; D63; G53; G51; 330; Financial literacy; Household finance; Wealth inequality; Income inequality; RIF regressions